A COMPREHENSIVE APPROACH: REVEALS CONSERVATION EDUCATION IN COLLEGE (Proceedings of the International Conference on Education, 2018)
This research aimed to determine the application of conservation cadre in the Faculty of Economics, State University of Semarang. This research used qualitative descriptive method. Informants consisted of conservation group and 28 students majoring in economic education. Data collection techniques used observation, documentation, interviews and document analysis. Activities in data analysis were data reduction, display data, and conclusion drawing / verification. Data validity applied source and methodological triangulation. The findings of this research showed that the knowledge and understanding of the students about the Rector regulation of the State University of Semarang, Number 22 of 2009 about State University of Semarang as Conservation University and Rector Regulation Number 6 of 2017 about Spirit Conservation showed only 11.11%, other findings showed that students still threw inappropriate garbage, smoking in campus areas, not upholding courtesy culture, the use of motor vehicles within the campus and less cultivate energy efficiency.
Keywords: character; conservation education; ethics; culture